The Mental and Cognitive Consequences of Smartphones and Modern Gaming Consoles on Children from Different Environments - Jawad, Aseel Hafedh; Al-Kazazz, Zainab Kareem; AlKhafaji, Naiel A. K. (American Journal of Biodiversity, 2025)
Two hundred smartphones -heavy children between the ages of two to twelve took part in this study. The parents of research participants gave permission for their children to participate through questionnaire distribution. The participants comprised sixty percent children who exceeded five years of age within this study. Roughly 54% of participants identified as female while the rest belonged to the male population. Among the children participating in this research, the percentage of video game users in urban environments exceeded that of those in rural environments, reaching 66%.The parents in this study possessed advanced educational backgrounds with bachelor degrees or above as their highest qualification; these degrees were held by 38.0% of mothers and 36.0% of fathers. The high educational expectations for these children positively reflect their educational environment. Children whose parents work outside the home environment showed an increase in the use of smartphones and video games, with smartphone usage reaching 42% and video game usage reaching 78%.Research data showed most participants lived in households of the middle social class. According to the survey results smartphones alongside other mobile devices for gaming purposes are utilised by 96 percent of children but only 4 percent of children avoid gaming through mobile devices. Most households owned multiple telephones (58%) along with nearly 78% of children constantly using them while a majority of participants experienced mood improvement following phone usage for at least two years (52%). (Survey Results) The research demonstrated that 56 percent of children possessed deficient intelligence combined with attention deficits. The research showed that finger difficulties develop in fifty percent of children because of excessive toy play and seventy percent of youngsters face dry eyes along with persistent drowsiness because of electronic device radiation. Studies demonstrate that 93% of people experience sadness together with anxiety. A phone addiction made 72% of surveyed youngsters experience headaches. An extensive study confirms that lengthy phone habits among children produce wide-ranging physical and mental medical complications. Parents need to make every attempt to prevent their children from utilization of smartphones while providing phone usage authorization only during emergencies. Children need specified utilization of smartphones times and they should be aware of what will happen in the short term and long term because of how they use their smartphones.